Selective C–N coupling reaction of diaryliodonium salts and dinucleophiles. (22nd March 2017) - Ma, Chang; Wu, Xufeng; Zeng, Qingle; Zhou, Lihong; Huang, Yi
Abstract : Ligand-free copper-catalyzed selective N -arylation of dinucleophiles including chiral α-amino amides with diaryliodonium salts as aryl electrophile equivalents was realized. Diaryliodonium salts prefer to react with dinucleophiles at the site of stronger basic amino groups. Abstract : N -Aryl-α-amino amides including their chiral isomers have demonstrated important applications as pharmaceutical drugs; however, to date, a one-step synthetic route for them still remains to be developed. Herein, an efficient ligand-free copper-catalyzed selective C–N coupling reaction of diaryliodonium salts and dinucleophiles under mild conditions was realized. Diaryliodonium salts prefer to react with dinucleophiles at the site of stronger alkalic amino groups. Thus, a general aliphatic amino-selective N -arylation of α-amino amides was disclosed. Additionally, copper-catalyzed N -arylation of diaryliodonium salts afforded the same products as obtained via palladium-catalyzed reactions of aryl halides.